2003
DOI: 10.1097/01.asn.0000046062.85721.ac
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin A Receptor Blockade and Endothelin B Receptor Blockade Improve Hypokalemic Nephropathy by Different Mechanisms

Abstract: Abstract. Hypokalemia causes renal tubulointerstitial injury with an elevation in renal endothelin-1 (ET-1). It was hypothesized that hypokalemic tubulointerstitial injury is ameliorated by the blockade of ET-A receptors (ETA), whereas ET-B receptor (ETB) antagonism may exacerbate the injury, because ETB is thought to mediate vasodilation. Rats were fed a K ϩ -deficient diet alone (LC) or with an ETA-selective antagonist ABT-627 (LA) or an ETB-selective antagonist A-192621 (LB) for 8 wk. Control rats were on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Our data indicate that macrophage infiltration is increased in the renal cortex of diabetic rats and attenuated by treatment with ABT-627. This is consistent with reports that ET A receptor blockade suppresses macrophage infiltration in the renal cortex of rats with aldosterone-induced hypertension (25) and hypokalemia-induced renal tubulointerstitial injury (26). Previous studies have shown that macrophage infiltration precedes development of structural changes in the diabetic kidney (15,16).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data indicate that macrophage infiltration is increased in the renal cortex of diabetic rats and attenuated by treatment with ABT-627. This is consistent with reports that ET A receptor blockade suppresses macrophage infiltration in the renal cortex of rats with aldosterone-induced hypertension (25) and hypokalemia-induced renal tubulointerstitial injury (26). Previous studies have shown that macrophage infiltration precedes development of structural changes in the diabetic kidney (15,16).…”
Section: Discussionsupporting
confidence: 92%
“…ET-1 promotes macrophage infiltration in the rat kidney (25), and ET A receptor blockade suppresses macrophage infiltration in the renal cortex in nondiabetic nephropathies (26) and attenuates the increase in TGF-␤ mRNA in glomeruli from diabetic rats (27).…”
mentioning
confidence: 99%
“…Mice were treated from 5 to 16 wk of age. The dosages of ABT-627 and A-192621 chosen were shown to be effective in previous studies (28). Mice were housed at constant temperature (21°C) and humidity (45%) on a 12-h light/dark cycle and had free access to drinking water and standard laboratory diet.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Microarray gene expression. Total RNA was extracted from glomerular samples by the acid guanidine-phenol-chloroform method, using Trizol reagent (Life Technologies) (20). We essentially followed the procedures described in detail in the GeneChip expression analysis manual (Affymetrix, Santa Clara, CA).…”
mentioning
confidence: 99%
“…Quantitative RT-PCR. We reverse transcribed 2.5 g of total RNA using Ready-To-Go (Amersham Pharmacia Biotech, Piscataway, NJ) (20). TaqMan real-time quantitative PCR was performed and analyzed according to the manufacturer's instructions (Applied Biosystems, Foster City, CA) (24).…”
mentioning
confidence: 99%